2019
DOI: 10.1111/nmo.13684
|View full text |Cite
|
Sign up to set email alerts
|

GHSR‐1 agonist sensitizes rat colonic intrinsic and extrinsic neurons to exendin‐4: A role in the manifestation of postprandial gastrointestinal symptoms in irritable bowel syndrome?

Abstract: Background Patients with irritable bowel syndrome (IBS) may experience postprandial symptom exacerbation. Nutrients stimulate intestinal release of glucagon‐like peptide 1 (GLP‐1), an incretin hormone with known gastrointestinal effects. However, prior to the postprandial rise in GLP‐1, levels of the hunger hormone, ghrelin, peak. The aims of this study were to determine if ghrelin sensitizes colonic intrinsic and extrinsic neurons to the stimulatory actions of a GLP‐1 receptor agonist, and if this differs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 59 publications
(130 reference statements)
1
15
0
Order By: Relevance
“…The peak of circulating GLP-1 levels coincides with postprandial symptom manifestation in patients with IBS 12 and in addition to its role as an incretin hormone, GLP-1 also modifies GI function, 13 both in healthy controls 46 and in patients with IBS. [14][15][16] Given our previous work, 10 where we determined that fasting GLP-1 levels are decreased in diarrhea-predominant…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The peak of circulating GLP-1 levels coincides with postprandial symptom manifestation in patients with IBS 12 and in addition to its role as an incretin hormone, GLP-1 also modifies GI function, 13 both in healthy controls 46 and in patients with IBS. [14][15][16] Given our previous work, 10 where we determined that fasting GLP-1 levels are decreased in diarrhea-predominant…”
Section: Discussionmentioning
confidence: 94%
“…Factors such as food, bile acids, antibiotics and infections, gender, and adverse psychosocial events, particularly in early childhood, are all implicated in alterations in the gut epithelial barrier. 10 Glucagon-like peptide-1 (GLP-1), which is released from intestinal L cells in response to the arrival of nutrients in the intestinal lumen, 11 is a circulating satiety hormone with a peak concentration that coincides with IBS postprandial symptom manifestation. Combined with microbial changes these results in abnormal gut secretory and sensorimotor function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Furthermore, in vivo investigations in Wistar-Kyoto rats found that Ex-4 alone normalized stress-induced defecation rates, but there were no additional effects of IL-6. 9 The current study has examined potential cross-communicationbetweenagonistsfortheIL-6andGLP-1receptors, both of which are expressed on intrinsic 12,26 and extrinsic 34 gut neurons. We also assessed how such interactions could modify colonic secretory and contractile function and we investigated if regional afferent signaling from the colon reflected the evoked changes in colonic function.…”
Section: Discussionmentioning
confidence: 99%
“…18 In contrast to the inhibitory effects in the proximal intestine,GLP-1hasbeenfoundtoenhancecolonictransitviaavagally mediated signaling mechanism. 19 Given the acute exacerbation of IBS symptoms in the post-prandial period, [20][21][22] and GLP-1-evoked changes in motility observed in patients with IBS as well as healthy individuals, [23][24][25] this gut hormone may be important in mechanisms underlyingboweldysfunction.Indeed,furtherevidencetosupport this supposition includes suppressed circulating levels of GLP-1 in diarrhea-predominant IBS patients 26 and the improvement in vis-ceralpainandgutspasmsinIBSpatientstreatedwithaGLP-1mimetic. 27,28 We have reproduced the positive effects of GLP-1 on gutfunctionintheWistar-KyotoratmodelofIBS 9 and used healthy Sprague-Dawley rats colons to further explore the mechanisms of action underlying these beneficial effects.…”
Section: Introductionmentioning
confidence: 99%